Against metasemantics-first moral epistemology - Hambly, Jesse; Yeo, Shang Long (The journal of ethics, 2025)
Moral metasemantic theories explain how our moral thought and talk are about certain properties. Given the connection between what our moral terms are about and which moral claims are true, it might be thought that metasemantic theorising can justify first-order ethical conclusions, thus providing a novel way of doing moral epistemology. In this paper, we spell out one kind of argument from metasemantic theories to normative ethical conclusions, and argue that it fails to transmit justification from premises to conclusion. We give three reasons for this transmission failure, which together pose a serious challenge to such metasemantic arguments.